Contrasting solid-state structures of trithiocyanuric acid and cyanuric acid - Guo, F.; Cheung, E. Y.; Harris, Kenneth D. M.; Pedireddi, V. R. (Crystal Growth & Design, 2006)
Although trithiocyanuric acid (TTCA) has been investigated widely as an agent in the formation of molecular cocrystals, the crystal structure of pure TTCA has never been determined. Attempts to grow crystals of pure TTCA by crystallization from solution invariably lead to the formation of solvate cocrystals, and desolvation of these materials leads to polycrystalline powder samples. In this paper, we report the structure determination of pure TTCA directly from powder X-ray diffraction data, using the direct-space genetic algorithm technique for structure solution followed by Rietveld refinement. The structure presents interesting contrasts to that of the oxygen analogue, cyanuric acid, and alludes to the possibility that both compounds might be capable of exhibiting polymorphism.